Perspektif Hukum terhadap Maraknya Kasus LGBT di Indonesia - Iqbal Wahyu Permana (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
One of the hottest issues currently rife in Indonesia is regarding sexual deviations known as LGBT (Lesbian, Gay, Bisexual, and Transgender/Transsexual). LGBT itself in Indonesia is certainly much opposed by society. This research was conducted using the literature study method, an approach that focuses on analyzing existing literature to collect, understand, and evaluate information related to the topics discussed. The results obtained in this study are that LGBT is an activity that is not in accordance with existing laws in Indonesia according to a legal perspective LGBT is deviant, LGBT also spreads many sexually transmitted diseases while the factors that cause someone to become LGBT are genetics, environment and traumatic experiences.